Survey of Knowledge Transformation Among Nursing Students During The Online Learning Methods - Suhartini Ismail (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2022)
ABSTRACT Introduction: Learning from conventional methods is transformed into online methods. These changes encourage new adaptations of technology to support the continuity of the learning process. The online learning process in Indonesia has not been implemented optimally, due to the unpreparedness of teachers and learners. The adaptation process that there are obstacles has an impact on the transformation of student knowledge with online learning methods. Aim: The purpose of this research to describe the knowledge transformation among nursing students during the online learning methods.Methods: Research method was descriptive survey. The total sample of Sampling with total 128 bachelor students at nursing program, Faculty of Medicine, Universitas Diponegoro. The data was taken using the Constructivist Online Learning Environment Survey (COLLES) questionnaire, includes relevance, reflective thinking, inter-activeness, tutor support, peer support, and interpretation. Data analysis used distribution frequency, boxplot, and quartile.Results: The highest components were in the relevance component (16.90 ± 1.915) and the lowest reflective thinking component (14.55 ± 2.255) and inter-activeness (14.55 ± 2,559). Overall, the transformation of nursing students' knowledge with the majority of online learning methods in the category of less than 70 respondents (54.7%). Conclusion: The nursing students can increase their knowledge transformation by being more active in giving and responding to opinions, improving critical thinking skills and praising each other's contributions between friends during learning. Lecturers can enhance the ability to create a creativity, innovative, and interactive learning process.